ANALISIS ATURAN ASOSIASI KESALAHAN STATISTIKA SISWA KELAS X-11 SMA NEGERI 10 SAMARINDA BERDASARKAN KRITERIA WATSON - Novri, Ivan; Rizki, Nanda Arista (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
Mathematics plays an important role in forming systematic thinking patterns, logic, and financial management skills. However, many students have difficulty in understanding mathematical concepts due to various factors, which affect the success of learning. This study aims to identify and classify common errors of class X-11 students of SMA Negeri 10 Samarinda in solving statistics problems using mixed quantitative and qualitative methods. solving statistics problems using mixed methods, namely quantitative and qualitative. Using the apriori algorithm with a minimum support of 20% and 80% confidence, four types of errors were found that were often made by students, namely incorrect data errors, procedural errors, missing conclusions, and skill hierarchy problems. Data analysis and interviews showed a strong correlation between these errors, where errors in data collection often lead to data manipulation and incorrect conclusions. To overcome this problem, the school has implemented more effective learning strategies, such as additional guidance, material adjustments, and contextual approaches. These strategies are expected to improve students' conceptual understanding, reduce errors, and improve academic achievement in statistics.